Scientific Basis and Principles of Methods of Teaching Mother Tongue - Ergashovna, Gaffarova Dildora (European Journal of Life Safety and Stability (2660-9630), 2022)
The methodology of teaching native language as a methodical science should provide ways in which teaching in school can explain the social role of har comprehensive cognition that will guarantee good development of students' speech. Hence, speech cultivation is an important function of the school.